Exploring computer ethics issues in Malaysia - Masrom, Maslin (International Association for Computer Information Systems, 2010)

(untitled)
In modern society nowadays, the development of information technology (IT) is indispensable to life. The use of IT has provided advantages for people, organizations, and society as a whole. Nevertheless, the widespread and rapid use of IT in society has exacerbated existing ethical issues or dilemmas, and also led to the emergence of new ethical issues such as unauthorized access, software piracy, internet pornography, privacy protection, information gaps, and many others. This paper presents a pilot study using a questionnaire administered to Malaysian students of higher education. Although there are many computer ethics issues, we confine our study of ethical issues to three main issues, namely accuracy, privacy and pirating of intellectual property. Several computer ethics scenarios that relate to the accuracy, privacy and intellectual property are also present in this paper.